pH-dependent regulation of a potassium channel protein encoded by a Chlorella virus PBCV-1 - Horváth, Ferenc (Acta Biologica Szegediensis, 2002)
In our project we studied a K+ channel, Kcv, encoded by a large Chlorella virus, PBCV-1. We investigated the pH dependency of the channel. The data reveal a weak dependency of the channel conductance on extracellular and intracellular pH .